Evaluation of policy in the vocational education system revitalization in Indonesia: Examining the teaching factory readiness of industry - Bernadetta Quinta Pradipta; Fajar Bambang Hirawan; Safendrri Komara Ragamustari (Jurnal Pendidikan Vokasi, 2021)
A future forecast for 2030-2040 predicts that Indonesia will face a demographic bonus, in which the productive aging population is greater than the unproductive age population. Graduates are expected to compete for a job on the national and international levels. It is a challenge where the Indonesian government began to enforce revitalization towards industries to collaborate with schools, and industries are expected to contribute to the implementation of the teaching factory, as both can contribute a mutual advantage in the long run. This research aims to illustrate the Indonesian government's progress, starting from 2016-2019, on revitalizing the vocational education system. This research highlights a qualitative research approach with a micro-level case study, using the teaching factory implementation parameter in VHS Suryacipta to find industries' readiness based on their perspectives, expectations, and challenges. The findings indicate the government effort has successfully improved the revitalization program. However, it still lacks field implementation. VHS Suryacipta still lacks collaboration follow-up with the industries, and the social mores of Karawang traditional society be the main factor behind the high unemployment rate. Other factors are the industries' capacity for employment, confidentiality aspect, misperception between industries and local government. Industries find difficulties matching with government agenda, which revealed that industries are not ready for collaboration.